IMAGING GLOBAL CHEMICAL AND THERMAL HETEROGENEITY IN THE SUBCONTINENTAL LITHOSPHERIC MANTLE WITH GARNETS AND XENOLITHS: GEOPHYSICAL IMPLICATIONS - O'Reilly S.Y.; Griffin W.L. (My University, 2006)
Suites of mantle-derived xenoliths in volcanic rocks provide estimates of the geothermal gradient and composition of the subcontinental lithospheric mantle (SCLM) at the time of the volcanic eruption. The development of single-grain thermometry and barometry, applied to xenocryst minerals in volcanic rocks, has greatly expanded the number of localities for which such data can be obtained and made it feasible to map the geology of the SCLM on a broader scale, both vertically and laterally. From garnet xenocrysts, it is possible to derive profiles showing mean values of olivine composition, bulk-rock composition, density and seismic velocities, as well as geotherm parameters and constraints on the thickness of the SCLM. Geochemical profiles, coupled with Re-Os dating of peridotites and their enclosed sulfide minerals, show that Archean or Proterozoic SCLM is preserved at shallow levels beneath many areas of younger tectonothermal age; this implies rapid vertical variations in Vs and Vp with depth, which may affect seismic interpretations. Data from several hundred localities worldwide define a secular evolution in the composition of the SCLM, related to the tectonothermal age of the overlying crust. Archean SCLM is typically strongly depleted in basaltic components, highly magnesian and thick (160-250 km), and has low geotherms; Phanerozoic SCLM is typically fertile (rich in basaltic components), Fe-rich, thin (50-100 km) and has a range of high geotherms; Proterozoic SCLM (much of which may be reworked Archean mantle) tends to be intermediate in all respects. The correlated variations in SCLM fertility, lithospheric thickness and geotherm reinforce the effects of each on seismic velocity, and produce more rapid lateral variations in seismic response than would result from thermal effects alone. These correlations are the key to using seismic tomography images to map the lateral extent of different types of SCLM. © 2006 Elsevier B.V. All rights reserved.
Keywords: GEOTHERMS; LITHOSPHERE MAPPING; MANTLE GEOPHYSICAL PROPERTIES; MANTLE HETEROGENEITY; SUBCONTINENTAL LITHOSPHERIC MANTLE; Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей